Sustainable Municipal Solid Waste Management: A Local Issue with Global Impacts - Abu-Qdais, Hani; Kurbatova, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint focuses on applied research in the field of solid waste management as a local issue with global dimensions. The role of circular economy practices to achieve sustainable waste management is highlighted. Furthermore, modeling techniques to assess the impacts of various waste treatment options are demonstrated. A waste-to-hydrogen energy option using metal scrap is evaluated. On a regional level, four articles from the Middle East and North Africa (MENA) region highlight the challenges and opportunities in the field of municipal solid waste management. Options for marine plastic reduction are highlighted. Factors and actors for the management and use of bio-solids are another topic that is covered in the reprint.